Improving Speed and Security When Sharing Protected Health Information of Deceased Organ Donors. (September 2019) - Trageser, Jeffrey; Davidson, Judy E.
Because extensive data from medical records are gathered by organ procurement teams, the process of data transfer between sites created a data security risk. This includes the use of fax machines, courier services, and employees' vehicles. Even health records transmitted over public Wi-Fi become at risk for a data breach. The Plan-Do-Study-Act method for performance improvement was used to address this time-consuming and labor-intensive process. A secured virtual private network from within the donor hospital site setting was developed to improve the transfer of images and data. The goal was to improve the process and increase data security. Once the new network was in place, the process steps decreased and eliminated data vulnerability. Average process time decreased by approximately 1 hour. Organs procured increased from pre (expected 3, observed 2) to post (expected 3, observed 5) implementation of the new process.